Evaluating potential benefits of the use of RFID, EPCglobal, and ebXML in the pharmaceutical supply chain. (3rd December 2012) - Guido, Anna Lisa; Mainetti, Luca; Patrono, Luigi
This paper attempts to evaluate the impact of radio frequency identification (RFID) technology, EPCglobal and ebXML on some business processes that are critical to the success of the pharmaceutical supply chain. Particular attention is focused on the wholesaler because it represents a particular stress point in terms of constraints and product flow. A quantitative and qualitative analysis of some current (AS IS) supply chain processes was performed on a big pharmaceutical wholesaler. It allowed us to identify some critical factors in the main business processes. In order to guarantee an efficient item-level tracing system in the whole supply chain, a re-engineering procedure has been defined exploiting an approach based on the combined use of RFID, EPCglobal, and ebXML. The key performance indicator (KPI) method has been chosen to carry out the analysis of the potential benefits by using an empirical method based on the living laboratory approach. This rigorous experimental approach, performed in a controlled test environment, allowed us to derive a realistic estimate of the selected performance indicators for the reengineered (TO BE) model.